Fatty Acid And Mineral Composition Of Some Agro Morphologically Distinct Quality Germplasm Of Indian Mustard (Brassica Juncea L.) (Applied Biological Research, 2019)
Indian mustard (Brassica juncea L.) which occupies largest area among the all  oleiferous Brassicas, is an important source of nutritionally important fatty  acid and micronutrients for animal including humans. The present study was  aimed to evaluate the fatty acid and mineral composition of 30 agro morphologically distinct quality germplasm of Indian mustard. The quality  germplasms were evaluated for fatty acid profiling by injecting methyl ester  sample into SP-2300 (2%) + SP-2310 (3%) packed silica column. Micro nutrients were determined by atomic absorption spectrophotometric method.  Fatty acid variability in quality germplasm revealed the erucic acid content of
Keywords: Fatty acid profiling; germplasm; Indian mustard; mineral composition; quality